Contactless High Dynamic-Range Blood Pressure Estimation by Pulse Morphological Features Based on Accurate Doppler Radar Detection - Zheng, Zhi; Dong, Shuqin; Shi, Haotian; Wang, Bo; Zhou, Zhiying; Guo, Yongxin (IEEE transactions on microwave theory and techniques, 2025)
Blood pressure (BP) can be estimated contactlessly based on Doppler wrist pulse (DWP) detection. However, this technique faces the challenge of interferences from the respiratory and its harmonic components, which can limit the accuracy of the BP estimation. This article first presents an adaptive respiratory harmonic filtering (ARHF) technique, aiming to mitigate the interference of respiration on the wrist pulse signal. Also, a customized 24-GHz continuous wave radar system with high linearity and a high gain antenna is used for better DWP detection. Second, a novel radar-based BP estimation model based on multidimensional morphological features extraction is proposed for high-accuracy and high-robustness BP estimation. In a stationary BP estimation experiment with eight subjects over three consecutive days, the proposed method demonstrates an average mean error and standard deviation of 2.60~± ~7.89 mmHg and 1.01~± ~2.84 mmHg in the sitting posture for systolic and diastolic blood pressure (SBP and DBP), respectively, achieving the highest estimation accuracy among the recent contactless radar-based BP detection. Additionally, a specific BP fluctuation range experiment is conducted to continuously measure BP, including varying BP fluctuations across five stages. In the worst case scenario, the proposed method exhibits SBP and DBP errors of 2.50~± ~2.98 and 8.34~± ~9.86 mmHg, respectively, affirming the robustness of the proposed technique. The experimental findings highlight the feasibility and reliability of the DWP extraction and subsequent contactless BP estimation techniques in the healthcare domain.